Outcome of Surgical Treatment of Spondylolisthesis by Decompression, Stabilization with Transpedicular Screws and Rods and Posterior Lumbar Interbodyfusion - Saha, Apel Chandra; Masud, Md Hasan (BIRDEM Medical Journal, 2017)
Background: Spondylolisthesis means forward shift of upper vertebral column over the lower vertebra. Most of the spondylolisthesis patients can be successfully treated by conservative treatment. A small but significant number of cases need surgical intervention. Design and capability of spinal instruments have drastically changed the principle of correction of spondylolisthesis by surgical interventions for better functional outcome. The objectives of this study were to assess surgical outcome, complications and return to normal activity of spondylolisthesis patients by posterior approach. Methods: This was a prospective interventional study, carried out at NITOR and different private hospitals in Dhaka from October 2012 to December 2014. Total number of patients was 12, who underwent posterior decompression and stabilization with transpedicular screws and rods and posterior lumbar interbody fusion (PLIF).Patients were followed up for a period of six months to one year. Functional outcome was evaluated by using Modified Oswestry Low Back Pain Disability Questionnaire. Results : Among 12 patients 5 were males and 7 were females, age ranged from 21-70 years with a mean age 43 ±7 years. Three patients (25%) had grade I, 8 patients (66.67%) had grade II and 1 patient (8.33%) had grade III spondylolisthesis. Follow up period was 6 months to 1 year. According to Modified Oswestry Low Back Pain Disability Questionnaire,it was observed that out of 12 patients 3 patients (25%) had excellent, 8 patients (66.67%) had better and 1 patient (8.33%) had worse functional outcome.In this study overall a satisfactory (excellent and better) result was found in 11 (91.68%) patients and unsatisfactory (unchanged and worse) result in 1 (8.33%) patient. Dural tear occurred in 1 patient (8.33%). Dural tear was repaired with 5/ 0 vicryl and there was no cerebro spinal fluid leakage. One patient (8.33%) developed foot drop that was treated surgically later on. Conclusion: Based on the results shown above, it is concluded that surgical treatment of spondylolisthesis by decompression, stabilization with transpedicular screws and rods and PLIF is a safe, effective and acceptable modality of treatment. Birdem Med J 2018; 8(1): 21-25